Pengaruh Kepribadian Neuroticism Dan Kesepian Dengan Kecenderungan Nomophobia Pada Mahasiswa - Merli Amprilia Putri; Asri Mutiara Putri; Prida Harkina (Program Studi Psikologi Islam, 2025)
This study aims to determine the influence of neuroticism personality traits and loneliness on the tendency of nomophobia among university students. Nomophobia refers to the excessive anxiety or fear experienced when individuals are unable to access or use their smartphones, a common condition among students in the digital era. Neuroticism is characterized by emotional instability, while loneliness reflects emotional and social isolation.This research employed a quantitative approach using a survey method. A total of 110 students from Malahayati University in Bandar Lampung were selected through convenience sampling. The instruments used included the Nomophobia Questionnaire, the Neuroticism Scale, and the UCLA Loneliness Scale . Data were analyzed using multiple linear regression.The results showed that neuroticism and loneliness significantly influenced nomophobia (F = 9.720; p < 0.05). Partially, neuroticism had a significant effect on nomophobia (β = 0.381; p = 0.002), while loneliness did not show a significant effect (β = 0.161; p = 0.143). The coefficient of determination (R²) was 11.8%, indicating that both independent variables contributed 11.8% to the nomophobia tendency.Thus, it can be concluded that neuroticism plays a crucial role in influencing nomophobia among students. Individuals with high neuroticism tend to experience greater anxiety when separated from their smartphones. Keywords : Neuroticism, Loneliness, Nomophobia, University Students